Al-A’ZAMĪ DAN FENOMENA QIRAAT ALQURAN: ANTARA MULTIPLE READING DENGAN VARIANT READING - Khaeruddin Yusuf (Hunafa: Jurnal Studia Islamika, 2014)
Absract: This article discusses one of the phenomena in the sciences of the Quran employing the point of view of  the contemporary muslim scholar, Muḥammad Muṣṭāfā al-A’zamī. He asserted  that one of the entrances used by the Orientalist to assault the authenticity of the Qur'an was through qiraat phenomenon. Al-A’zamī critisized the Orientalist’s views in terms of methodology, of analysis process and of  study results. The nonexistance of a dot and diacriticals did not become a problem for the text of the Koran since the system of the true recitation was taught by the prophet through memorization. The true system of reciting the Qur’an had already existed  in the minds of the Companions of the Prophet. The terms used in recitation cannot also be separated from Al-A’zamī’s attention. He said  that the term  “multiple” (many) recitaions is more properly used  than the  term “variant” (various) recitations.Kata Kunci: qiraat, multiple qiraat, tanda titik, diakritikal